THE NEEDS OF YOUNG LEARNERS FOR DEVELOPING E-BOOK FOR TEACHING ENGLISH-SPEAKING SKILLS - Mandaria, Ruth Nova; Karani , Elanneri; Bungai, Joni (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2021)
Speaking English is one of the most significant communication skills that one is required in digital era of the 21th century. Therefore, it is necessary to develop speaking skill earlier for young learners who learn English at elementary school. This article reports a survey to explore the needs of young learners at elementary schools who learn English in digital era. The research subjects were four teachers of English and 258 students of the fourth grade at elementary schools in Palangka Raya. The research instruments are developed in the form of an interview guide and a questionnaire using google form for collecting data concerning the needs of young learners in learning English. Percentage and qualitative description are employed to expose the survey outcomes. The results are used the basis later for designing and developing an e-book of English (based on local content) for young learners who are learning English at elementary schools in Palangka Raya, Central Kalimantan.